Penerapan Fungsi-Fungsi Manajemen dalam Meningkatkan Mutu Pendidikan Islam Di SMA Swasta PAB 1 Medan Estate - Fitra Amalia Harahap; Adelia Fitri; Aidatul Fauziah; Dina Oktapia; Rizki Akmalia; Amiruddin Siahaan; Fauzan Azrohid (Journal on Education, 2023)
Improving the quality of education cannot be separated from the quality of human resources owned. Therefore, Educational Institutions must also be thus able to meet the needs of human resources both in quantity and quality by increasing educational resources to supply human resource needs in accordance with the demands and improving the local education process by developing the necessary elements and supporting elements. Improving quality learning needs to use strategies that can be applied by each institution by taking into account the characteristics of the institution. With quality human resources, it is expected that educational institutions will become institutions that are able to effectively face future challenge. Quality standards for the learning process must also be established, in the sense that management needs to apply quality standards for the learning process that are expected to be effective to optimize the learning process and to produce appropriate outputs, namely mastering these quality standards.